2015
DOI: 10.1016/j.mcn.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The Dlx5 and Foxg1 transcription factors, linked via miRNA-9 and -200, are required for the development of the olfactory and GnRH system

Abstract: During neuronal development and maturation, microRNAs (miRs) play diverse functions ranging from early patterning, proliferation and commitment to differentiation, survival, homeostasis, activity and plasticity of more mature and adult neurons. The role of miRs in the differentiation of olfactory receptor neurons (ORNs) is emerging from the conditional inactivation of Dicer in immature ORN, and the depletion of all mature miRs in this system. Here, we identify specific miRs involved in olfactory development, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 100 publications
(161 reference statements)
2
50
1
Order By: Relevance
“…This targeting strategy was designed to generate a bicistronic messenger RNA (mRNAs), encoding both endogenous Foxg1 and the transgenic Cre . Moreover, the targeting strategy was designed to insert the IRES-Cre and frt-flanked PGKneo cassettes 27bp after the stop codon of the full length Foxg1 gene, thus maintaining the previously described miRNAs targeting sites in 3′UTR of Foxg1 gene (e.g., miR-9 and miR-200 ) (Choi et al, 2008; Garaffo et al, 2015; Shibata et al., 2011, 2008). Importantly, this strategy did not incorporate an exogenous polyadenylation (polyA) sequence, which causes abnormal miRNA regulation in the Foxg1-Cre line due to the deletion of Foxg1 3′UTR from the Cre coding mRNA (Miyoshi and Fishell, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This targeting strategy was designed to generate a bicistronic messenger RNA (mRNAs), encoding both endogenous Foxg1 and the transgenic Cre . Moreover, the targeting strategy was designed to insert the IRES-Cre and frt-flanked PGKneo cassettes 27bp after the stop codon of the full length Foxg1 gene, thus maintaining the previously described miRNAs targeting sites in 3′UTR of Foxg1 gene (e.g., miR-9 and miR-200 ) (Choi et al, 2008; Garaffo et al, 2015; Shibata et al., 2011, 2008). Importantly, this strategy did not incorporate an exogenous polyadenylation (polyA) sequence, which causes abnormal miRNA regulation in the Foxg1-Cre line due to the deletion of Foxg1 3′UTR from the Cre coding mRNA (Miyoshi and Fishell, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The dysregulation of expression in the Foxg1-Cre line precludes its use as a telencephalon specific Cre driver line, as ectopic Cre activity is invariably observed in regions around the mid- and hindbrain (Achim et al, 2012; Fuccillo et al, 2004; Hébert and McConnell, 2000; Kasberg et al, 2013; Li et al, 2008, 2012; Ma et al, 2002; Zembrzycki et al, 2007). The reasons behind these inconsistent Cre activities are not completely known but could be due in part by deletion of functional endogenous microRNAs (miRNAs) sites in the Foxg1 3′UTR from the Cre coding messenger RNA (mRNA) (Miyoshi and Fishell, 2012) that would normally repress Foxg1 expression (Choi et al, 2008; Garaffo et al, 2015; Shibata et al, 2011, 2008). In addition, the Foxg1-Cre allele contains a PGK-neo cassette, which in some case has been shown to result in unpredictable Cre activity (Iwasato et al, 2004; Pham et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies previously reported and validated the efficiency and specificity of the miR-9 MO (45,48–51). Embryos were injected at the one-cell stage with 2 pmole of the miR-9 or control MO.…”
Section: Methodsmentioning
confidence: 97%
“…Table 1 summarizes the results of a myriad of studies, which suggest that miR-200 members play a critical role in the differentiation and proliferation of neurons [8,9,10], podocyte differentiation [11], taste bud formation [12], insulin signaling pathway regulation in the control of fat body and body size [7], and for the hormonal regulation of endometrial stromal decidualization [13,14] during embryo implantation [15]. …”
Section: Introductionmentioning
confidence: 99%